Ecuador: Ciclo Económico y Política Fiscal - Pacheco, Diana (2006)
Although, great part of the economists has centered their studies in the Monetary Policy, the study of the Fiscal Policy lately has been developed with the purpose of inferring in certain areas where the monetary aggregates have not been able to take part. So, the present investigation tries to define the stabilizing effects of fiscal aggregates in the economy, the impact over time of the fiscal handling and the possible implications over the society of the political management. It is the analysis of the economy in movement, the fluctuations of the GDP and its possible causes given the handling of fiscal tools.